CO2 Emissions Avoided Through the use of Biodiesel in the Brazilian Road System - Soares Murta, AurÃ©lio Lamare; de Freitas, Marcos AurÃ©lio Vasconcelos (International Journal of Energy Economics and Policy, 2018)
For several years, the use of oil for driving vehicles, generating power and many other activities has caused the world to become highly dependent on it, which is running out. Biodiesel stands out among these alternatives as a potential replacement for petroleum diesel, and it is obtained through the transesterification of vegetable oils or animal fat. In addition to being renewable, biodiesel reduces Brazil’s dependence on petroleum and emits less greenhouse gases such as CO2, which is the focus of this article. Based on calculations performed considering petrodiesel consumption in Brazil, this study aims at quantifying CO2 emissions until 2025 and the avoided emissions when methyl biodiesel produced from soybean oil is used as part of the fuel, considering the blend percentages determined by the Brazilian government for the established period. Keywords: Biodiesel; Road transportation; Environmental JEL Classifications: Q01; Q42; L71